Transient Global Amnesia : From Patient Encounter to Clinical Neuroscience - Larner, A.J (Springer International Publishing : Imprint: Springer, 2017)
This brief, accessible book covers all aspects of transient global amnesia (TGA). First, it deals with the history of TGA before moving on to clinical and diagnostic features, and differential diagnosis. The investigation and management of TGA is then discussed, followed by treatment and prognosis. Each of the chapters is devoted to a practical and structured overview of the particular topic, with use of case studies to illustrate the material. Based in part on the author's experience of TGA cases over 15 years and in part on a review of the published literature, this book will hopefully enlighten clinicians from a broad range of medical backgrounds on the clinical features, investigation, and pathogenesis of TGA. Transient Global Amnesia is aimed at any clinician with an interest in, or who encounters patients with, acute amnesia: neurologists, general physicians, old age psychiatrists, geriatricians, clinical neuropsychologists, and primary care physicians, as well as other professions allied to medicine with similar interests, such as members of memory assessment teams.
Keywords: Medicine.; Geriatrics.; Neurology.; Primary care (Medicine).; Psychiatry.; elektronické knihy; electronic books